Insights on the structure-activity relationship of peptides derived from Sticholysin II - Oliveira, Aline Lima de; Cilli, Eduardo Maffud [UNESP]; Ros, Uris; Crusca, Edson [UNESP]; Lanio, Maria Eliana; Alvarez, Carlos; Schreier, Shirley; Pertinhez, Thelma Aguiar; Spisni, Alberto (Wiley-Blackwell, 2018)
Sticholysin II (StII) is a pore-forming actinoporin from the sea anemone Stichodactyla helianthus. A mechanistic model of its action has been proposed: proteins bind to cell membrane, insert their N-termini into the lipid core and assemble into homo-tetramer pores responsible for host-cell death. Because very likely the first 10 residues of StII N-terminus are critical for membrane penetration, to dissect the molecular details of that functionality, we studied two synthetic peptides: StII(1-30) and StII(16-35). They show diverse haemolytic and candidacidal activity that correlate with distinct orientations in SDS micelles. NMR shows that StII(1-30) partly inserts into the micelle, while StII(16-35) lays on the micelle surface. These results justify the diverse concentration dependence of their candidacidal activity supposing a different mechanism of action and providing new hints on StII lytic activity at molecular level. Biotechnological application of these peptides, focused on the development of therapeutic immunocomplexes, may be envisaged.
Keywords: candidacidal activity; hemolytic activity; NMR; pore formation; structure-activity relationship